FACTORS ASSOCIATED WITH OUTCOMES IN LAPAROSCOPIC COLONIC SURGERY: A ANALYSIS OF EARLY EXPERIENCE - ULLAH , R; BABAR , Y; SHAH , M; KHAN , A (Biological and Clinical Sciences Research Journal, 2024)
Laparoscopic-assisted colonic (LAC) surgery has gained acceptance for various colonic diseases, yet comprehensive studies on diverse patient demographics and procedural outcomes are essential. This study aimed to evaluate 96 LAC surgeries, examining patient characteristics, surgical procedures, conversion factors, and perioperative outcomes. A one-year case series conducted at multiple centers, including the Department of General Surgery, MRHSM Hospital Pabbi Nowshera, Jinnah Teaching Hospital Peshawar, Cat C Hospital Tangi Charsadda, and DHQ Hospital Daggar Buner, Khyber Pakhtunkhwa, Pakistan in the duration from January 2023 to December 2023. Demographic diversity, prevalent colonic conditions, and detailed surgical procedures were analyzed. Conversion factors and perioperative outcomes, aligned with international standards, were documented. The cohort displayed diverse demographics, with predominant male participation. Surgical interventions, notably right hemicolectomy, demonstrated variable distributions. Conversion to open surgery was infrequent and primarily associated with locally advanced disease. Perioperative outcomes aligned with global findings, emphasising reduced pain, accelerated recovery, and shorter hospital stays. This study contributes valuable insights into the safety and efficacy of LAC across varied colonic diseases, supporting its role in modern colorectal surgery. The findings underscore the importance of careful patient selection and affirm the procedure's favourable perioperative profile.